Endocannabinoid system and mood disorders: priming a target for new therapies - Micale, Vincenzo; Di Marzo, Vincenzo; Sulcova, Alexandra; Wotjak, Carsten T; Drago, Filippo (Pharmacology & therapeutics, 2013)
The endocannabinoid system (ECS), comprising two G protein-coupled receptors (the cannabinoid receptors 1 and 2 [CB1 and CB2] for marijuana's psychoactive principle ∆(9)-tetrahydrocannabinol [∆(9)-THC]), their endogenous small lipid ligands (namely anandamide [AEA] and 2-arachidonoylglycerol [2-AG], also known as endocannabinoids), and the proteins for endocannabinoid biosynthesis and degradation, has been suggested as a pro-homeostatic and pleiotropic signaling system activated in a time- and tissue-specific way during physiopathological conditions. In the brain activation of this system modulates the release of excitatory and inhibitory neurotransmitters and of cytokines from glial cells. As such, the ECS is strongly involved in neuropsychiatric disorders, particularly in affective disturbances such as anxiety and depression. It has been proposed that synthetic molecules that inhibit endocannabinoid degradation can exploit the selectivity of endocannabinoid action, thus activating cannabinoid receptors only in those tissues where there is perturbed endocannabinoid turnover due to the disorder, and avoiding the potential side effects of direct CB1 and CB2 activation. However, the realization that endocannabinoids, and AEA in particular, also act at other molecular targets, and that these mediators can be deactivated by redundant pathways, has recently led to question the efficacy of such approach, thus opening the way to new multi-target therapeutic strategies, and to the use of non-psychotropic cannabinoids, such as cannabidiol (CBD), which act via several parallel mechanisms, including indirect interactions with the ECS. The state of the art of the possible therapeutic use of endocannabinoid deactivation inhibitors and phytocannabinoids in mood disorders is discussed in this review article.
Keywords: Disease Models, Animal; Receptors, Cannabinoid; antidepresiva; modely nemocí na zvířatech; poruchy nálady; Mood Disorders; Anti-Anxiety Agents; Animals; lidé; receptory kanabinoidní; endokanabinoidy; Antidepressive Agents; anxiolytika; zvířata; Humans; Endocannabinoids